Repetitive Transcranial Magnetic Stimulation Target Location Methods for Depression - Zhang, Min; Wang, Runhua; Luo, Xin; Zhang, Si; Zhong, Xiaomei; Ning, Yuping; Zhang, Bin (Frontiers in Neuroscience, 2021)
Major depressive disorder (MDD) is a substantial global public health problem in need of novel and effective treatment strategies. Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive and promising treatment for depression that has been approved by the U.S. Food and Drug Administration (FDA). However, the methodological weaknesses of existing work impair the universal clinical use of rTMS. The variation of stimulated targets across the dorsolateral prefrontal cortex may account for most of the efficacy heterogeneity of rTMS. Many rTMS target location methods for MDD have been developed in recent decades. This review was conducted to assess this emerging field and to improve treatment outcomes in clinical practice.